The effects of 2 levels of the inspired oxygen fraction on blood gas variables in propofol-anesthetized dogs with high intracranial pressure - Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Nunes, Newton [UNESP]; Lopes, Patrícia Cristina Ferro [UNESP]; De Almeida, Ricardo Miyasaka [UNESP]; Neto, Gláucia Bueno Pereira [UNESP]; De Souza, Ana Letícia Groszewicz [UNESP]; Belmonte, Emílio De Almeida [UNESP] (My University, 2009)
The influence of 2 different levels of the inspired oxygen fraction (FiO2) on blood gas variables was evaluated in dogs with high intracranial pressure (ICP) during propofol anesthesia (induction followed by a continuous rate infusion [CRI] of 0.6 mg/kg/min) and intermittent positive pressure ventilation (IPPV). Eight adult mongrel dogs were anesthetized on 2 occasions, 21 d apart, and received oxygen at an FiO2 of 1.0 (G100) or 0.6 (G60) in a randomized crossover fashion. A fiberoptic catheter was implanted on the surface of the right cerebral cortex for assessment of the ICP. An increase in the ICP was induced by temporary ligation of the jugular vein 50 min after induction of anesthesia and immediately after baseline measurement of the ICP. Blood gas measurements were taken 20 min later and then at 15-min intervals for 1 h. Numerical data were submitted to Morrison's multivariate statistical methods. The ICP, the cerebral perfusion pressure and the mean arterial pressure did not differ significantly between FiO2 levels or measurement times after jugular ligation. The only blood gas values that differed significantly (P < 0.05) were the arterial oxygen partial pressure, which was greater with G100 than with G60 throughout the procedure, and the venous haemoglobin saturation, that was greater with G100 than with G60 at M0. There were no significant differences between FiO2 levels or measurement times in the following blood gas variables: arterial carbon dioxide partial pressure, arterial hemoglobin saturation, base deficit, bicarbonate concentration, pH, venous oxygen partial pressure, venous carbon dioxide partial pressure and the arterial-to-end-tidal carbon dioxide difference.